North American and Norwegian Chronic Wasting Disease Prions Exhibit Different Potential for Interspecies Transmission and Zoonotic Risk. (24th July 2021) - Pritzkow, Sandra; Gorski, Damian; Ramirez, Frank; Telling, Glenn C; Benestad, Sylvie L; Soto, Claudio
Abstract: Background: Chronic wasting disease (CWD) is a rapidly spreading prion disorder affecting various species of wild and captive cervids. The risk that CWD poses to cohabiting animals or more importantly to humans is largely unknown. Methods: In this study, we investigated differences in the capacity of CWD isolates obtained from 6 different cervid species to induce prion conversion in vitro by protein misfolding cyclic amplification. We define and quantify spillover and zoonotic potential indices as the efficiency by which CWD prions sustain prion generation in vitro at expenses of normal prion proteins from various mammals and human, respectively. Results: Our data suggest that reindeer and red deer from Norway could be the most transmissible CWD prions to other mammals, whereas North American CWD prions were more prone to generate human prions in vitro. Conclusions: Our results suggest that Norway and North American CWD prions correspond to different strains with distinct spillover and zoonotic potentials. Abstract : We investigated in vitro spillover and zoonotic potential of CWD from various cervid species. Our results suggest that Norway CWD prions have a higher potential to infect other animals, but North American CWD appears more prone to generate human prions.